The dsRBP Staufen2 governs RNP assembly of neuronal Argonaute proteins. Issue 12 (10th June 2022) - Ehses, Janina; Schlegel, Melina; Schröger, Luise; Schieweck, Rico; Derdak, Sophia; Bilban, Martin; Bauer, Karl; Harner, Max; Kiebler, Michael A
Abstract: Mature microRNAs are bound by a member of the Argonaute (Ago1-4) protein family, forming the core of the RNA-induced silencing complex (RISC). Association of RISC with target mRNAs results in ribonucleoprotein (RNP) assembly involved in translational silencing or RNA degradation. Yet, the dynamics of RNP assembly and its underlying functional implications are unknown. Here, we have characterized the role of the RNA-binding protein Staufen2, a candidate Ago interactor, in RNP assembly. Staufen2 depletion resulted in the upregulation of Ago1/2 and the RISC effector proteins Ddx6 and Dcp1a. This upregulation was accompanied by the displacement of Ago1/2 from processing bodies, large RNPs implicated in RNA storage, and subsequent association of Ago2 with polysomes. In parallel, Staufen2 deficiency decreased global translation and increased dendritic branching. As the observed phenotypes can be rescued by Ago1/2 knockdown, we propose a working model in which both Staufen2 and Ago proteins depend on each other and contribute to neuronal homeostasis.